Ombitasvir/paritaprevir/ritonavir + dasabuvir ± ribavirin for treatment of chronic hepatitis C 1 genotype in the Republic of Belarus - Danilau, Dzmitry; Malich, Nadzeya; Litvinchuk, Dzmitry; Karpov, Igor (Clinical and Experimental Hepatology, 2017)
Aim of the study is to evaluate real-world efficacy of the ombitasvir/ paritaprevir/ ritonavir + dasabuvir ± ribavirin for treatment of chronic hepatitis C 1 genotype. Material and methods: The study included 27 patients according to inclusion criteria. Main laboratory studies were performed in all patients at the baseline and during the treatment. Results: Efficacy of the antiviral therapy was assessed by measuring the SVR12 and the SVR24 along with measuring of viral load during the treatment. The SVR12 and SVR24 rate was 100% (27/27). Discussion : The results of the treatment were comparable to the results of pivotal, large-scale, randomized clinical trials. There were no serious adverse events during the treatment.